Improved production and quality of peppers irrigated with regenerated water by the application of 24-epibrassinolide - Pintó-Marijuan, Marta (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2023 The Authors. Published by Elsevier B.V. All rights reserved.